ENGLISH WISE QUOTES AS MEDIA FOR STUDENTS’ VOCABULARY MASTERY AT SMP NEGERI 35 MAKASSAR - A. Adinda Harliany Suci Ramadhani; Restu Januarty; Andi Hamzah Fansury (Lembaga Jurnal FKIP Universitas Bosowa, 2022)
This research focuses on the students' English vocabulary mastery through wise quotes. The purpose of this research was to find out whether with wise quotes, students' vocabulary understanding will increase or not. This research used a pre-experimental research method by giving a pre-test and post-test. The sample of this research is class VIII.7 SMP Negeri 35 Makassar in the academic year 2021/2022, totaling 20 people. This research uses SPSS v.16 which can show the results of the analysis of a significant increase in test scores and can prove the influence of this research. The results of this study indicate that the significance value is 0.000, which is smaller than 0.05, which means that this research has a significant effect. Therefore, it can be concluded that wise quotes have an increasing effect on students' vocabulary comprehension, and it can be seen that through wise quotes, students can become more motivated in the learning process.